Pengembangan E-Modul Ajar Konsep Dasar Matematika SD Berbasis Realistic Mathematics Education Berpadu Problem Based Learning dengan Menggunakan Flipbook - Andi Marshanawiah; Sartika Arifin; Fauziah Hakim; Nursyam Anaguna; Muliani Muliani (Departement of Mathematics Education, 2023)
This study aimed to determine the process of developing teaching e-modules, the feasibility of teaching e-modules, and the results of evaluating student responses to the development of teaching e-modules for Basic Concepts of Elementary Mathematics based on Realistic Mathematics Education combined with Problem-Based Learning using Flipbook. The type of research used is Research and Development (R&D) research with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research was tested on 55 3rd-semester students in 2022/2023 PGSD Department of Gorontalo State University academic year. The instruments used during the research were material expert validation questionnaires, media expert validation questionnaires, and student response evaluation questionnaires. The material expert validation questionnaire, media expert validation questionnaire, and student response evaluation questionnaire were analyzed quantitatively using a Likert scale. The results of material expert validation obtained an average percentage of component feasibility of 96% with very strong interpretation criteria, the results of media expert validation obtained an average percentage of component feasibility of 97.88% with very strong interpretation criteria and the results of evaluating student responses to teaching e-modules obtained an average percentage of 86.86% with very strong interpretation criteria. So that the results of the study indicate that the teaching e-module for Basic Concepts of Elementary Mathematics based on Realistic Mathematics Education combined with Problem-Based Learning using Flipbook is said to be feasible and qualified to be used as teaching material in the learning process of the Basic Concepts of Elementary Mathematics course.